Professional Identity of School Teachers in Southern Cities of Russia - Lyudmila V. Klimenko; Oksana Yu. Posukhova; Yulia K. Agryzkova (Социологическая наука и социальная практика, 2017)
This article analyzes the correlation between the age of school teachers in large and mid-size cities of Rostov region and their professional identity. According to the survey conducted among 1018 professionals, teachers don’t see their job as prestigious among the members of Russian society. These teachers rate their material and social well-being mostly as satisfactory. Most respondents are being subjected to precarization, which means that all types of their occupational load (e.g. accounting and reporting, preparing for and conducting classes with new training standards, forms and methods being introduced, non-school occupation, individual classes for students etc.) have been increasing over the last several years. Professional identity of the teachers weakens under these circumstances and becomes inferior to primordial (e.g. family, age) and worldview identities. This is especially noticeable among young professionals teaching in large cities and ageing professionals teaching in mid-size cities.